Combined Influence of Pit Size and Fertilizer on Survival and Growth of Cassia siamea in Degraded Soil - Pant, N. C.; Pandey, D. K.; Sonkar, S. D.; Banerjee, S. K. (Indian Forester, 1995)
The influence of different pit sizes with or without fertilizer application on survival and growth of thirty months' old Cassia siamea in degraded soil was studied. The survival and plant height significantly increased as tlie size of pit increased with or without fertilizer. Urea over 25 g pit-1 applied in smaller pits < 30 cm3 ) adversely affected the survival of plants, where as, response of phosphorus as a whole was observed to be positive. Among forty possible treatment combinations (5 pit sizes and. 8 fertilizer levels) the best treatment combination was 45x45x60 em pit size with 75 g urea and 75 g single superphosphate per pit for better survival and higher growth of plants.